2017
DOI: 10.1017/jog.2017.6
|View full text |Cite
|
Sign up to set email alerts
|

Spectral measurements of surface hoar crystals

Abstract: ABSTRACT. Surface hoar crystals are common on the surface of mountain snow covers. Once buried, layers of large plate-shaped surface hoar crystals are prone to releasing dangerous snow-slab avalanches. Since snow microstructure influences the optical properties of snow, remote sensors could potentially detect the formation of surface hoar and other snow types associated with avalanche release. The spectral reflectance of 377 snow samples was measured with a field spectrometer between 750 and 2500 nm, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…However, it is possible to detect a small difference between certain spectral bands, such as in the 1000-1100 nm and 1200-1300 nm bands, in which different groups of snow with close or homogeneous physical characteristics can be distinguished. These spectral reflectance values show that the reflectance changes throughout the wavelength regions as snow ages [6,33]. Indeed, snow samples that were newly deposited on the snowpack (precipitation particles, decomposing, and fragmented precipitation particles) and that had a low to medium density (50-200 kg m −3 ) had higher reflectance values.…”
Section: Descriptive Analysismentioning
confidence: 90%
See 3 more Smart Citations
“…However, it is possible to detect a small difference between certain spectral bands, such as in the 1000-1100 nm and 1200-1300 nm bands, in which different groups of snow with close or homogeneous physical characteristics can be distinguished. These spectral reflectance values show that the reflectance changes throughout the wavelength regions as snow ages [6,33]. Indeed, snow samples that were newly deposited on the snowpack (precipitation particles, decomposing, and fragmented precipitation particles) and that had a low to medium density (50-200 kg m −3 ) had higher reflectance values.…”
Section: Descriptive Analysismentioning
confidence: 90%
“…The snow cover, also called snowpack, is the set of snow layers that pile up on the ground throughout winter [ 5 ]. This snow cover is highly variable due to the complex distribution of precipitation, wind, and radiation after snow deposition [ 6 ]. Each layer is separated from the previous one by a superposition plane.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that, as surface hoar grows, the snow surface becomes less and less Lambertian but that the geometry (illumination and viewing), at which the reflectance is maximum or minimum is difficult to predict. Horton and Jamieson (2017) used reflectance measurements and investigated the potentiality of normalised difference indices calculated from conical reflectance measurements at two wavelengths (860 and 1310 nm) to classify different crystal morphologies. They concluded that the bidirectional reflectance properties for different snow types must be investigated further.…”
mentioning
confidence: 99%